Operation Management in Sport Venue - Jayawardhana, Irman; Fidinansyah, Farazandi (Prasetiya Mulya Publishing, 2025)
In this paper, the authors have chosen to examine the operational strategic evaluation of Old Trafford Stadium. Although there are studies discussed about using operation management for managing venue, but there are still limited studies that have discovered clearly the implementation of sport venue management. The authors have used qualitative methods by tour observation in Old Trafford and secondary data from websites and academic books. In addition, through using these methods, the writers described the implementation of operation management, service process, operation performance, and operation strategy in Old Trafford. These four elements have proved to give impact on the revenues of the venue itself. To sum up, the findings proved that these four points are essential for Old Trafford, to gain more revenues. In contrast, commercialization is the only negative point that have been found by the writers that affected in customer satisfaction, caused by poor atmosphere in the stadium